Grand challenges in low temperature plasmas - Lu, XinPei; Bruggeman, Peter J.; Reuter, Stephan; Naidis, George; Bogaerts, Annemie; Laroussi, Mounir; Keidar, Michael; Robert, Eric; Pouvesle, Jean-Michel; Liu, DaWei; Ostrikov, Kostya (Ken) (Frontiers in Physics, 2022)
Low temperature plasmas (LTPs) enable to create a highly reactive environment at near ambient temperatures due to the energetic electrons with typical kinetic energies in the range of 1 to 10 eV (1 eV = 11600K), which are being used in applications ranging from plasma etching of electronic chips and additive manufacturing to plasma-assisted combustion. LTPs are at the core of many advanced technologies. Without LTPs, many of the conveniences of modern society would simply not exist. New applications of LTPs are continuously being proposed. Researchers are facing many grand challenges before these new applications can be translated to practice. In this paper, we will discuss the challenges being faced in the field of LTPs, in particular for atmospheric pressure plasmas, with a focus on health, energy and sustainability.